Respostas

2014-06-24T11:17:19-03:00
X^2 + 8x + 16 = 9x + 22
x^2 - x - 6 = 0
delta = 1 - 4*1*(-6)
delta = 1 + 24
delta = 25

x = 1+/-5 dividido por 2          x1 = 3            x2 = -2
1 5 1
2014-06-24T11:26:54-03:00
Equação de 2 grau(x+4)^2= 9x+22

(x+4)² = 9x + 22
(x+4)(x+4) = 9x + 22
x² + 4x + 4x + 16 = 9x + 22
x² + 8x + 16 = 9x + 22-----------------------igualar a ZERO
x²  + 8X + 16 - 9X - 22 = 0----------------------------------------ARRUMAR a casa
x² + 8x - 9x + 16 - 22 = 0
x² - x - 6 = 0
a = 1
b = - 1
c = - 6
Δ = b² - 4ac
Δ = (-1)² - 4(1)(-6)
Δ = + 1 + 24
Δ = 25---------------------------√25 = 5
se
Δ > 25
então(Baskara)

x = - b - + √Δ/2a
x' = -(-1) - √25/2(1)
x' = + 1- 5/2
x' = - 4/2
x' =- 2

x" = -(-1) + √25/2(1)
x" = + 1 + 5/2
x" = 6/2
x" = 3

logo, temos   x = - 2  ou x = 3

2 5 2